Quantitative analysis of PBAT microplastics and their degradation products in soil by mass spectrometry - Zhuyao Hua; Ya Li; Xin He; Fengxiao Zhu; Sha Chang; Jijie Kong; Changyin Zhu; Chao Wang; Shiyin Li; Huan He; Cheng Gu (Eco-Environment & Health, 2025)
Global production of biodegradable plastics is increasing, but the degradation behavior of microplastics derived from these items in soil is still scarcely reported. In this study, a method for quantifying soil poly(butylene adipate-co-terephthalate) (PBAT) microplastics was developed, and their degradation behavior in three different soils was investigated. PBAT was quantified by analyzing the content of the monomer terephthalic acid (TPA) released during thermally assisted alkali hydrolysis, using liquid chromatography-mass spectrometry (LC-MS). For alkali hydrolysis, the use of capped bottle, water bath (90 ​°C for 30 ​min), and ultrasonication (100 ​kHz for 15 ​min) allowed for high-throughput sample processing in comparison to the use of round-bottom flask, reflux condenser, and stirring heating mantle. After 150 days, 10.8%–11.0% of PBAT microplastics were degraded in the acidic and neutral soils, while 17.1% were degraded in the alkaline soil, in line with the greatest lipase activity changes in the alkaline soil. This may be due to the fact that alkaline conditions favor initial depolymerization of PBAT, facilitating subsequent microbial attack. PBAT degradation products were also monitored, using solvent extraction combined with LC-MS and gas chromatography-mass spectrometry analysis. It was found that butanediol (up to 1580 ​μg/kg) accumulated to a higher level than TPA (about 50 ​μg/kg), especially in acidic and alkaline soils. Overall, this study, for the first time, precisely quantified the degradation of PBAT microplastics in soil. Further study is needed to better understand the fate of biodegradable microplastics in the soil environment and whether they will persist.